Detection of iron emission lines and a temperature inversion on the dayside of the ultra-hot Jupiter KELT-20b - Yan, Fei; Reiners, A.; Pallé, E.; Shulyak, D.; Stangret, M.; Molaverdikhani, Karan; Nortmann, L.; Mollière, Paul Maurice; Henning, Thomas; Casasayas-Barris, N.; Cont, D.; Chen, G.; et al. (Astronomy and astrophysics, 2022)
Ultra-hot Jupiters (UHJs) are gas giants with very high equilibrium temperatures. In recent years, multiple chemical species, including various atoms and ions, have been discovered in their atmospheres. Most of these observations have been performed with transmission spectroscopy, although UHJs are also ideal targets for emission spectroscopy due to their strong thermal radiation. We present high-resolution thermal emission spectroscopy of the transiting UHJ KELT-20b/MASCARA-2b. The observation was performed with the CARMENES spectrograph at orbital phases before and after the secondary eclipse. We detected atomic Fe using the cross-correlation technique. The detected Fe lines are in emission, which unambiguously indicates a temperature inversion on the dayside hemisphere. We furthermore retrieved the temperature structure with the detected Fe lines. The result shows that the atmosphere has a strong temperature inversion with a temperature of 4900 ± 700 K and a pressure of bar at the upper layer of the inversion. A joint retrieval of the CARMENES data and the TESS secondary eclipse data returns a temperature of K and a pressure of bar at the lower layer of the temperature inversion. The detection of such a strong temperature inversion is consistent with theoretical simulations that predict an inversion layer on the dayside of UHJs. The joint retrieval of the CARMENES and TESS data demonstrates the power of combing high-resolution emission spectroscopy with secondary eclipse photometry in characterizing atmospheric temperature structures.